Formulation of Brown Rice Flour Cookies Combination with Bay Leaf Extract (Syzygium Polyanthum) as a Functional Food - Cantika Zaddana; Almasyhuri Almasyhuri; Dena Alfitri; Sara Nurmala; Fitria Dewi Sulistiyono (Journal of Global Nutrition, 2021)
Functional food is a processed food that contains more than one component which based on scientific studies has benefits for the health of the body. Functional foods can be classified into several types based on the food source and the processing method. This study aims to determine the proximate composition, fiber and flavonoid contents, and the effect of the varying concentrations of the bay leaf extract on the cookies. Three formulas of bay leaf extract were made with different concentrations. The formula I use 3.0%, formula II uses 2.5%, and formula III uses 2%. The results of the hedonic test analysis showed that the best formula was formula III with a concentration of 2% bay leaf extract. These results indicate that the concentration of the bay leaf extract affects the taste and aroma of the cookies, even though it does not affect the color and texture. By using formula III, proximate tests were also carried out on these cookies to determine water content, ash content, protein content, fat content, and carbohydrate content. The proximate test results showed that the cookies met the quality requirements of cookies set by SNI 2973-2011. In formula III cookies, the content of flavonoids was 1.4278%, and food fiber was 6.04%.